Characteristics of HRV patterns for different yoga postures - Pitale, Rahul; Tajane, Kapil; Phadke, Leena; Joshi, Aniruddha; Umale, Jayant (2014 Annual IEEE India Conference (INDICON), 2014)
Human heart rate fluctuates in a complex and non-stationary manner, due to continuous influences from autonomic nervous system and other factors (harmones, temp, etc) on the sinoatrial node (S.A) (Pacemaker of the heart). ANS dysfunction is known to be associated with various cardiovascular and lifestyle diseases. The importance of traditional ancient Indian practice like Yoga has increased significantly due to the observed beneficial effects of it in various lifestyle diseases. Preliminary studies have shown that yoga may have its beneficial effect by influencing autonomic nervous system. Heart rate variability (HRV) is a most promising predictive and prognostic marker of autonomic (ANS) activity. HRV is analyzed by time and frequency domain parameters (Fast Fourier Transform). Being linear parameters these are not able to extract full information regarding the non linear behavior of heart rate fluctuations. In this paper, we propose to analyze HRV by using linear as well as non-linear methods during different yogaasanas. These mathematical models will be useful to understand the underlying physiological mechanisms during different yogasanas.
Keywords: ECG; HRV; Poincare plot; Recurrence plot; Yogasanas